2019
DOI: 10.1115/1.4045046
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength Behaviors of Ultra-High-Temperature Materials

Abstract: Ultra-high-temperature materials have been widely used as key components in high-end equipment. However, the existing studies are mainly conducted at room and moderate temperatures. Besides, they are mainly carried out by experiments. Theories on the temperature dependence of fracture strength are rarely reported. In this work, experimental methods for the ultra-high-temperature tensile properties of advanced materials and the elastic–plastic properties of coatings are developed, respectively, based on inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Existing studies have focused on the mechanical performance of materials, and most of them have studied plain and satin textile materials. 17,18 The weaving parameters of fabric have significant impact on the ablation performance of TPM. For example, the effect of weaving parameters on the ablation performance of plain and satin woven materials has been studied, and it has been shown that they do have a nonnegligible effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have focused on the mechanical performance of materials, and most of them have studied plain and satin textile materials. 17,18 The weaving parameters of fabric have significant impact on the ablation performance of TPM. For example, the effect of weaving parameters on the ablation performance of plain and satin woven materials has been studied, and it has been shown that they do have a nonnegligible effect.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the weaving parameters of fabric have significant influence on various properties of woven composites, such as strength, 14 surface friction, 15 impact, 16 and so forth. Existing studies have focused on the mechanical performance of materials, and most of them have studied plain and satin textile materials 17,18 . The weaving parameters of fabric have significant impact on the ablation performance of TPM.…”
Section: Introductionmentioning
confidence: 99%